Interpreting Non-Farm Participation and Its Welfare Outcomes: A Qualitative Study of Rural Farming Households in Gibe District, Hadiya Zone, SNNPR, Ethiopia - Ergicho, Yisihak (International Humanity Advance, Business & Sciences, 2025)
This study explores how rural farming households in Gibe District interpret their participation in non-farm activities and how such engagement influences their overall welfare. Using a qualitative research design grounded in sustainable livelihoods and diversification theories, the study draws on semi-structured interviews with household members engaged in various non-farm occupations. The findings reveal that non-farm work is perceived as a strategic complement to agriculture, enabling households to mitigate livelihood risks associated with land scarcity, market volatility, and climatic uncertainty. Participants consistently described non-farm income as contributing to multidimensional welfare improvements, including enhanced food security, educational access, healthcare affordability, and strengthened women’s decision-making power. However, these benefits are moderated by structural constraints such as unstable earnings, limited capital, and unequal access to profitable opportunities. The study contributes a novel interpretive perspective to the literature by emphasizing the meaning-making processes through which households evaluate welfare, moving beyond conventional economic indicators. The findings underscore the importance of integrated policy measures that expand equitable access to non-farm opportunities, strengthen rural financial systems, and support gender-responsive livelihood strategies.